Correctional Transgender Policy in Canada’s Federal Prison System - Foley, Gillian (Criminal justice policy review, 2024)
Since December 2017, Canada’s federal correctional system provides prisoners the opportunity to be assigned to living units according to their self-identified gender. Still organized around sex, conceptually and spatially, prison policies and procedures surrounding transgender prisoners require navigation to adhere to the rights of all prisoners. Based on interviews conducted between October 2019 and October 2021 with 74 correctional officers (COs) from the Canadian federal prison system, we discuss how correctional officers view and operationalize Canada’s transgender policy to understand its unintended consequences for both prisoners and prison staff. Unintended consequences revolve around the potential risk for prisoner victimization, prisoner pregnancy, lack of adequate housing, strip search complications, officers’ fear of being labeled transphobic, and uncertainty and discretion; all having effects on staff wellness. The policy, although well-intended, may potentially compromise prisoner safety, making correctional work even more stressful.